Physiological and microbiological studies of nectar xylose metabolism in the Namaqua rock mouse, Aethomys namaquensis (A. Smith, 1834) - Nicolson, Sue W. (University of Pretoria, 2013)
Thesis (PhD (Zoology))--University of Pretoria, 2007.